Sharia Compliance and Implementation of Zakat Distribution Governance (Case Study of Al-Hidayah Mosque Citeras Lebak Banten) - Siti Wardah Rizkiyah; Mila Azizah (Transpublika Publisher, 2026)
The implementation of zakat fund governance at the Dewan Kemakmuran Masjid (DKM) or Mosque Prosperity Council of the Al-Hidayah Mosque in Citeras, Lebak Banten, still operated within a traditional and poorly structured framework. This study aimed to analyze sharia compliance in the zakat distribution practices carried out by the Al-Hidayah Mosque Council (DKM) to zakat recipients (mustahik). This study combines field observations with doctrinal legal analysis using a qualitative normative-empirical methodology, with legal normativity analysis. The governance of zakat funds at the Al-Hidayah Mosque’s DKM remains largely traditional and has not fully aligned with sharia compliance principles, particularly in ensuring accurate targeting of zakat recipients (asnaf). Nevertheless, efforts have been made to adopt PSAK No. 109, which emphasizes accountability and transparency in zakat management. The mosque’s management also seeks to fulfill the mandate of Law No. 23 of 2011, Article 1, which defines zakat management as the planning, implementation, and coordination of zakat collection, distribution, and utilization. In practice, zakat distribution at Al-Hidayah Mosque has been directed to eligible asnaf groups, consistent with Article 27 of the same law, which allows zakat to be used productively to alleviate poverty and improve community welfare. However, zakat governance at the mosque still requires improvement, particularly through coordination with provincial and district/city BAZNAS, as mandated by Article 31 of Law No. 23 of 2011, which authorizes these institutions to collect and distribute zakat. The DKM of Al-Hidayah Citeras Lebak Mosque must also implement the Zakat Core Principles and strengthen zakat governance aspects.